Framing 'Asia': results from a visitor study at Rijksmuseum's Asian Pavillion - Löseke, Annette; Grasskamp, Anna (Aziatische kunst, 2014)
"FRAMING ‘ASIA’: RESULTS FROM A VISITOR STUDY AT THE RIJKSMUSEUM’S ASIAN PAVILION" published on 25 Jul 2014 by Brill.
Gesehen am 20.04.2020